Integrasi Nilai-Nilai Al-Qur’an dalam Pendidikan Islam Kontemporer di Era Disrupsi: Upaya Dalam Mewujudkan Pengembangan Peserta Didik Secara Holistik - Rahman; Khairuddin; Ahmad Ghozali Syafi’i; Perdamaian (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the strategic integration of Qur’anic values in contemporary Islamic education amid the dynamics of the disruption era, characterized by digital transformation, socio-cultural change, and shifts in knowledge paradigms. The urgency of internalizing Qur’anic values has intensified in response to growing challenges faced by students, including moral ambiguity, information overload, and declining spiritual awareness. Employing a descriptive qualitative approach based on a literature review, this study analyzes the relevance and implementation strategies of Qur’anic values within modern educational contexts. The findings indicate that core Qur’anic values—such as tawḥīd, integrity, compassion, justice, and social responsibility—serve as fundamental ethical foundations for developing students with holistic competencies. The study further reveals that effective implementation of these values requires transformative pedagogical innovations, including value-based learning, the integration of digital ethics, character-oriented curriculum design, and synergistic collaboration among teachers, families, and educational institutions. Moreover, Qur’an-based digital literacy is identified as a crucial preventive and constructive strategy for addressing digital risks while maximizing technological opportunities in Islamic education. This study concludes that the integration of Qur’anic values is not only relevant but essential for fostering resilient, ethical, and spiritually grounded students capable of navigating the complexities of contemporary life, thereby contributing to the development of holistic and sustainable Islamic education.